2011
DOI: 10.1007/s12070-011-0336-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Otitis Media with Effusion Among Primary School Age-Children and Etiopathogenic Examination

Abstract: A prevalence study was carried out in order to look into the etiopathogenic relation of otitis media with effusion (OME) in primary school-age children. The study included ENT examination and a questionnaire that was carried out in 4 randomly selected schools on 1,165 children. 143 of the cases (12.2%) had OME. A significant relation between OME and adenoid vegetation was found (P<0.01) while no significant relation between EOM and recurrent tonsillitis and allergic rhinitis was found (P>0.05). As a result, OM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 10 publications
2
15
1
Order By: Relevance
“…Among the 100 cases studied in present study, majority of them had grade 3 tonsillar hypertrophy (48%) followed by grade 2 tonsillar hypertrophy (46%) and grade 4 tonsillar hypertrophy was seen in only 6 cases (6%). 9 Here we can see grade 2 and 3 constitute around 94% which is comparable with Ajayan et al; where they got tonsillar hypertrophy of 2nd and 3rd grades to be most common grades together constituting around 90% of cases. They have stated that the effect of both obstruction and infection from tonsil and adenoid are seen to cause major ill effect nose and paranasal sinus, ET and middle ear cleft.…”
Section: Chronic Adenotonsillar Hypertrophy and Its Relationship Withsupporting
confidence: 87%
See 2 more Smart Citations
“…Among the 100 cases studied in present study, majority of them had grade 3 tonsillar hypertrophy (48%) followed by grade 2 tonsillar hypertrophy (46%) and grade 4 tonsillar hypertrophy was seen in only 6 cases (6%). 9 Here we can see grade 2 and 3 constitute around 94% which is comparable with Ajayan et al; where they got tonsillar hypertrophy of 2nd and 3rd grades to be most common grades together constituting around 90% of cases. They have stated that the effect of both obstruction and infection from tonsil and adenoid are seen to cause major ill effect nose and paranasal sinus, ET and middle ear cleft.…”
Section: Chronic Adenotonsillar Hypertrophy and Its Relationship Withsupporting
confidence: 87%
“…It is stated that a type B curve in tympanometry has an over 80% sensitivity of detection for OME. 9 Günel et al found type B tympanograms provided a sensitivity of 92.3% and a specificity of 91.9%. So, they suggested that tympanometry can make a more accurate diagnosis of pediatric OME in AH children with or without parental suspicion of HI.…”
Section: Tympanometry In Chronic Adenotonsillitismentioning
confidence: 98%
See 1 more Smart Citation
“…Screening surveys of children in good health ranging in age from infants to age five years show a 15% to 40% prevalence of middle-ear effusion. 6,[12][13][14][15][16][17][18][19][20][21] Among children examined at normal intervals for one year, 50% to 60% of child care center attendees 17 and 25% of school-aged children 22 had otitis media with effusion at some time during the examination period, with elevated incidence during the winter months. Population-based screening has not impacted short-term language outcomes 18 and we have not assessed its long-term effects in a randomized clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Otitis media is the most common childhood disease after viral upper respiratory tract infection. 8 OME is an inflammatory response of the middle ear characterized by tympanic cavity effusion and no symptoms of acute infection. OME is generally seen after acute otitis media (AOM) and a three-month-long course is defined as COME.…”
Section: Discussionmentioning
confidence: 99%